Taksonomi Kewenangan Psikolog - Supratiknya, Augustinus (Fakultas Psikologi Universitas Sanata Dharma, 2023)
Law number 23 of 2022 concerning “psychology education and services” stipulates that the division of qualifications among Psikolog Umum, Psikolog Spesialis, and Psikolog Subspesialis should be regulated in a specific Peraturan Pemerintah. This article proposes a Taxonomy of Qualifications of Psychologists based on the goals of the provision of psychological intervention (promotion, prevention, cure, rehabilitation, and palliation) as well as the degrees of the psychological problems (normal, mild, and severe) of clients.